Extraction of Starch from Taro (Colocasia esculenta) and Evaluating it and Further Using Taro Starch as Disintegrating Agent in Prazosin Hydrochloride Tablet Formulation with Over All Evaluation (International Journal of Scientific Research in Science and Technology, 2024)
Originating in Southeast Asia, taro (Colocasia esculent Linn.) is a tropical root that is grown vegetatively. It is produced throughout Africa and is ranked ninth among food crops worldwide. In tropical and subtropical regions, taro tubers constitute a staple diet and a significant source of carbohydrates for energy. The main reason it is grown is because its buried corms have a 1.2% content. In addition, potassium, copper, manganese, iron, phosphorus, zinc, niacin, and vitamin B6 are all abundant in taro. It is also a good source of thiamine, riboflavin, and other minerals. Aro is also useful for encasing flavoring components. To highlight taro starch in the realm of pharmaceutical research, more studies on the starch can be conducted and released onto the market. Taro has been employed in numerous industrial processes in addition to being used in culinary preparation. Taro starch granules are perfect for use in face powder and dusting solutions that use aerosol dispensing systems because of their minuscule size. Despite the aforementioned applications, large-scale starch extraction and use remain unusual. Consequently, this study may lead to more discussion and consideration of taro starch within the pharmaceutical research community.
Keywords: Tropical Root; Taro Tubers; Pharmaceutical Research; Starch Granules